Preoperative and intraoperative risk factors for acute kidney injury after hip fracture surgery: a cohort retrospective study - Bassem I. Haddad; Abdulrahman A. Alhajahjeh; Abdelrahman Altarazi; Layla El-Amayreh; Mohammad Hamdan; Batool AlQuabeh; Waid Abd Ul Ghani; Randa I. Farah (Renal Failure)
Introduction Hip fractures have several adverse effects on patients’ morbidity and mortality. Postoperative Acute kidney injury (AKI) is one of the complications that have a significant impact on the patient’s overall prognosis. We aimed to identify AKI risk after hip fracture surgery and the preoperative and intraoperative risk factors.Methodology We conducted a retrospective cohort study in a tertiary care hospital on adult patients who underwent surgery for hip fractures between January 2015 and August 2021. All clinical data were reviewed.Result A total of 611 patients were included (age = 76.44 ± 9.69 years). 126 (20.6%) of them developed AKI postoperatively. In multilinear logistic regression analysis, factors associated with postoperative AKI included eGFR [odds ratio (OR): 0.98; 95% confidence interval (CI): 0.97–0.99 with a p value .01], spinal anesthesia [OR: 1.78; 95% CI: 1.1–2.9 with a p value .01], and partial hip replacement (PHR) type of surgery [OR: 0.56; 95% CI: 0.32–0.96 with a p value .036]. The development of postoperative AKI was the strongest factor that increase mortality of the patients as the (HR = 2.42, CI 95% [1.57–3.74]; p value <.001).Conclusion In this study, we highlight that lower eGFR, and spinal anesthesia were associated with a higher risk of AKI, and PHR surgery has lower odds to develop AKI. Postoperative AKI is associated with a higher mortality rate after hip fracture surgery.